Origins and development of New Zealand English - Warren, Paul (International Journal of Language, Translation and Intercultural Communication, 2012)
This paper provides an overview of the chief characteristics of a relatively new variety of English, New Zealand English. After a brief historical sketch of the development of English in New Zealand, the paper highlights some of the grammatical patterns of the variety, before looking in more detail at the lexical features and characteristic pronunciations that make it a distinct variety. One of the significant infl uences on the development of New Zealand English has been contact with the Maori language and with Maori cultural traditions. This is refl ected in the presence of a large number of Maori words in common use in New Zealand English, as well as in the development of Maori English as an ethnic variety in New Zealand. Finally, the paper considers other sources of variation within New Zealand English, including early signs of regional diff erentiation as well as age- and gender-linked variation that have emerged in the patterns of change in progress that typify this new variety.